Nandrolone Stimulates Myod Expression During Muscle Regeneration in the Condition of Myonecrosis Induced by Bothrops jararacussu Venom Poisoning - Alves de Souza, Rodrigo Wagner [UNESP]; Goncalves, William [UNESP]; Garrido Cavalcante, Walter Luis [UNESP]; Dal Pai-Silva, Maeli [UNESP]; Gallacci, Marcia [UNESP] (Taylor & Francis Inc, 2010)
Myonecrosis with permanent loss of muscle mass is a relevant local toxic effect following envenomation with Bothrops jararacussu snake venom. Regeneration of adult skeletal muscle involves the activation of satellite cells, a process regulated by myogenic regulatory factors (MRF). MyoD is an MRF involved in both proliferation and differentiation of satellite cells. Androgens are modulators of skeletal muscle, known to increase muscle mass and strength. This study examined the hypothesis that anabolic androgens improve the muscle regeneration process in mice following envenomation by Bothrops jararacussu snake venom. Myonecrosis was induced by venom injection (30 g/50 l in physiological solution) over the extensor digitorum longus (EDL) muscles of mice. Nandrolone (ND) (6 mg/kg, sc) was administered after 12 h, 7 d, and 14 d following venom injection. The histological changes in EDL muscle at 1, 3, 7, and 21 d after muscle injury were analyzed by light microscopy. Cross-sectional areas of fibers were measured. MyoD was evaluated by immunofluorescence technique. Histological examination revealed the presence of a regeneration process in ND-treated animals, characterized by the appearance of some myotubes at 3 d, and numerous myotubes at 7 d from venom injection. Nandrolone treatment reduced the frequency of small fibers at 7 and 21 d after venom administration, and increased the frequency of large fibers at 7 d postinjury. Nandrolone also significantly augmented the expression of MyoD-positive cells at 7 and 21 d after envenomation. These results suggest that ND accelerates muscle regeneration and indicate the involvement of MyoD in this process.